Molecular aspects of COVID-19 and its relationship with obesity and physical activity: a narrative review - Lino, Ramon de Souza; Silva, Mariana Sousa de Pina; Jesus, Daniel Simões de; Macedo, Rodrigo Colares de; Lagares, Laura Souza; Santos, Felipe Nunes Almeida dos; Almeida, Luiz Alberto Bastos de; Bomfim, Eric Simas; Santos, Clarcson Plácido Conceição dos (São Paulo Medical Journal, 2023)
BACKGROUND: Severe acute respiratory syndrome coronavirus 2 has several mechanisms of action related to inflammatory responses, especially in individuals diagnosed with obesity. This hyperinflammatory clinical profile resulting from the association between obesity and coronavirus disease 2019 (COVID-19) may be attenuated by regular physical activity. OBJECTIVE: The aim of this study was to review the evidence on the consequences of physical inactivity and physical activity on COVID-19 in patients with obesity. DESIGN AND SETTING: Narrative review at the Bahiana School of Medicine and Public Health in Salvador, Brazil. METHODS: We searched evidence on the association of COVID-19 with physical activity and obesity using the following keywords: “covid-19,” “physical activity,” and “obesity”. The databases used were MEDLINE (PubMed), ScienceDirect, and Virtual Health Library. Studies published from 2019 to 2021 and available in Portuguese, English, and Spanish were included. The final search was conducted on September 26, 2021. RESULTS: We identified 661 studies in the database, among which 71 were considered for inclusion in the narrative review of the molecular aspects of COVID-19 and its relationship with physical activity and obesity. CONCLUSION: This literature review enabled the perception of the relationship between the molecular mechanisms of COVID-19 and obesity. Regular physical activity had various benefits for the inflammatory condition of the studied population, highlighting moderate-intensity.